Simulation of the thermal mechanism in semiconductors under action of pulsed electromagnetic field - Chumakov, V.I.; Slichenko, N.I.; Stolarhuk, A.V.; Egorov, A.M.; Lonin, Yu.F. (Вопросы атомной науки и техники, 2004)
The paper presents a model taking into account the time character of heat localization and distribution in semiconductor devices unlike the classical Wunsch-Bell linear model describing the thermal mechanism of EM-radiation
action on REA. The classification of action levels is given. The nonlinear model permitting to determine the time
boundary of heat propagation in the semiconductor device is presented. In the time range t>tcr a uniform volumetric
heating of the object takes place, and for t<tcr there is a heat localization in the range of energy release due to the lag
of the heat dissipation process behind the energy input process. Taking this into account one determines the energy
leading to irreversible results of action. The model allows one to determine the feeblest aspects of REA. В роботі, на відміну від класичної лінійної моделі Вунча-Белла, яка описує тепловий механізм впливу
ЕМ-випромінювання на РЕА, пропонується модель, що враховує часовий характер локалізації та
розповсюдження тепла в напівпровідникових пристроях. Дається класифікація рівнів впливу. Приводиться
нелінійна модель, яка дозволяє враховувати часову межу розподілення тепла в напівпровідникових
пристроях. В масштабі часу t>tкр має місце однорідний об’ємний розігрів об’єкту, а при t<tкр має місце
локалізація тепла внаслідок запізнення процесу тепловідводу від процесу енерговводу в області
енерговиділення. Виходячи з цього визначається енергія, що приводить до незворотних наслідків дії.
Модель дозволяє визначити найбільш слабкі місця РЕА і дозволяє спростити експериментальні
випробування елементної бази РЕА в цілому. В работе, в отличие от классической линейной модели Вунча-Белла, описывающей тепловой механизм
влияния ЭМ-излучения на РЭА, предлагается модель, учитывающая временной характер локализации и распространения тепла в полупроводниковых приборах. Дается классификация уровней воздействия. Приводится нелинейная модель, которая позволяет определить временную границу распространения тепла в полупроводниковом приборе. В диапазоне времен t>tкр имеет место однородный объемный разогрев объекта, а
при t<tкр происходит локализация тепла в области энерговыделения вследствие запаздывания процесса теплоотвода от процесса энерговвода. Исходя из этого, определяется энергия, приводящая к необратимым результатам воздействия.
Модель позволяет определить наиболее слабые места РЭА и позволяет упростить экспериментальные испытания элементной базы и РЭА в целом.